Establishment of Specialized Pediatric Palliative Home Care in the Medical Valley of the European Metropolitan Area Nuremberg - Hébert, Steven; Gravou-Apostolatou, Chara; Rascher, Wolfgang (Klinische Pädiatrie, 2017)
Background As part of the 2007 health reform in Germany the structure of outpatient palliative care for children and adolescents was adopted for the first time and then implemented in Erlangen-Nuremberg in 2009. Methods The introduction of Pediatric Palliative Home Care (PPHC) at the Hospital for Children and Adolescents at the University of Erlangen-Nuremberg was retrospectively analyzed between the years 2009 to 2014. Referring medical records (paper-based and electronic) were evaluated systematically. Results Considering 69 patients within this study, 44 (63.8%) died during the investigated period and 61% of these Patients deceased at home. 60 patients (87%) had a written emergency plan, which was jointly developed with patients and particularly their parents and relatives in cooperation with the PPHC team. Over the years and with increasing experience, the number and duration of emergency hospitalization decreased. Even complex therapies, such as patient-controlled analgesia with PCA pump could be implemented on an outpatient basis. Conclusion The descriptive cohort study demonstrates that palliative care for children, despite the medical and structural complexity is possible in an ambulatory setting. It allows a similar, if not better care, compared to inpatient palliative care for children and adolescents, not only for the affected patients, but also for their families.
EVALuna2:34224